Creative video competition: A new approach in nurturing national identity and citizenship among pre-diploma students - Ismail, Noraini; Sabri, Siti Hanisah; Iswadi Efendi, Muhammad Danish Amin; Mohamad Razali, Muhammad Afis Firdaus (2022)
The creative video competition is a teaching and learning initiative for the Introduction to Human Development Course (CTU001) in UiTM Perlis and it was implemented during the pandemic via an online platform. It aims to cultivate the values and identity of citizenship which is one of the important topics in the CTU001 course. Based on the old method, learning was through lectures in class and the assignments were assigned in written forms. With this competition, students do not have to be in class all the time but they have to prepare a video according to the theme that has been set in groups. Students are free to be creative and to present information through videos in front of eight jurors. This competition has successfully improved students' soft skills and knowledge. The findings of the survey showed that the students can understand well the values and identity of citizenship as well as they manage to cultivate good values in ensuring that the tasks given were implemented successfully. This competition program needs to be continued as an added value of teaching and learning in the CTU001 course especially during the implementation of Open Distance Learning (ODL).